The Influence of Price Perception and Social Media Communication on Purchase Intention Mediated By Brand Image and Trust Among Electric Motorcycle (Electric Vehicle) Consumers - Agus Agus (International Journal Labs, 2025)
Motorcycles have become an inseparable part of people's activities, especially for daily needs, such as in the midst of congestion and air pollution caused by motor vehicle emissions. Therefore, the existence of electric motorcycles is becoming increasingly important. Competition in the electric motorcycle industry is getting tighter, encouraging manufacturers to improve the image and quality of their products at more affordable prices in order to compete. The purpose of this study is to determine the influence of Price Perception and Social Media Communication on Purchase Intention Mediated by Brand Image and Trust in Electric Motorcycle Consumers in the city of Monokwari Papua. This study uses a quantitative method with primary data sources obtained from the distribution of questionnaires. The study population is electric motorcycle users in the city of Manokwari. The selection of respondents was carried out by a saturated non-probability sampling method with a total of 150 respondents. The data analysis method uses descriptive analysis and SEM-PLS analysis. The results of the study show that the variables of price perception and social media communication have a positive and significant effect on purchase intention through Brand Image and trust in Electric Motorcycle consumers in the city of Monokwari Papua.